Smiling for the Future: How School-Based Dental Initiatives Boost Oral Health in Pakistan - Abro, Preh Ayub; Durr-e-Sadaf, Durr-e-Sadaf; Bilal, Muhammad; Ahmed, Naseer; Rehman, Haris; Imran, Farrukh (Journal of Neonatal Surgery, 2025)
Introduction: Oral health problems, particularly dental caries and poor hygiene, are highly prevalent among school-going children in Pakistan. School-based interventions offer a practical approach to promote preventive oral health behaviors and reduce disease burden at an early age. Methodology: A quasi-experimental study was conducted among 300 children aged 6–12 years in selected schools of Karachi, Pakistan. A multistage sampling technique was used. Baseline data on oral hygiene practices and clinical parameters (DMFT/dmft and OHI-S indices) were collected, followed by a 3-month school-based dental intervention including oral health education, supervised toothbrushing, and screening. Post-intervention assessment was conducted using the same measures. Data were analyzed using SPSS version 26. Descriptive Statistics, Paired t-test, and Chi-square test were applied, with p<0.05 considered significant. Results: Significant improvements were observed in oral hygiene practices, with the proportion of children brushing twice daily increasing from 38% to 76% (p<0.001). Use of fluoride toothpaste increased, while sugary snack consumption decreased significantly (p<0.001). Mean DMFT/dmft scores reduced from 2.84 ± 1.12 to 2.10 ± 1.05, and OHI-S scores improved from 2.35 ± 0.76 to 1.42 ± 0.68 (p<0.001younger There was an increased improvement of behavior in children (p=0.041). Conclusion: School based dental programs have shown to be effective in enhancing oral-hygiene behavior and clinical outcomes among children and needs to be incorporated into the public health initiatives in Pakistan.